Nutritional and Functional Roles of Phytase and Xylanase Enhancing the Intestinal Health and Growth of Nursery Pigs and Broiler Chickens - Vitor Hugo C. Moita; Sung Woo Kim (Animals, 2022)
This review paper discussed the nutritional and functional roles of phytase and xylanase enhancing the intestinal and growth of nursery pigs and broiler chickens. There are different feed enzymes that are currently supplemented to feeds for nursery pigs and broiler chickens. Phytase and xylanase have been extensively studied showing consistent results especially related to enhancement of nutrient digestibility and growth performance of nursery pigs and broiler chickens. Findings from recent studies raise the hypothesis that phytase and xylanase could play functional roles beyond increasing nutrient digestibility, but also enhancing the intestinal health and positively modulating the intestinal microbiota of nursery pigs and broiler chickens. In conclusion, the supplementation of phytase and xylanase for nursery pigs and broiler chickens reaffirmed the benefits related to enhancement of nutrient digestibility and growth performance, whilst also playing functional roles benefiting the intestinal microbiota and reducing the intestinal oxidative damages. As a result, it could contribute to a reduction in the feed costs by allowing the use of a wider range of feedstuffs without compromising the optimal performance of the animals, as well as the environmental concerns associated with a poor hydrolysis of antinutritional factors present in the diets for swine and poultry.